A Note on the Crack Problem for a Nonhomogeneous Plane - Chaudhuri, P.K.; Ray, S. (Engineering Transactions, 1996)
A plane elasticity problem in a nonhomogeneous medium containing a crack has been considered. It is assumed that the medium has a constant Poisson’s ratio while the Young’s modulus varies exponentially both along and perpendicular to the length of the crack. The problem is solved by derivation of an integral equation and the effects of nonhomogeneity have been shown in tables and graphs.